2022
DOI: 10.1007/s11356-022-24096-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the composition, source, and stability of suspended particulate matter and sediment organic matter in Hulun Lake, China

Abstract: Sediment (SOM) and suspended particulate (SPOM) organic matters are two important organic matters in water. Their occurrence, migration and transformation, and stability have important effects on the environmental behaviors of carbon, nitrogen, phosphorus, and other pollutants in a water environment. The content, composition, fluorescence characteristics, source, and stability of SOM and SPOM in Hulun Lake, a typical lake in cold and arid region of China, were compared by sequential extraction, three-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
(57 reference statements)
0
0
0
Order By: Relevance
“…Autochthonous SPM production is imported from the resuspension of aquatic organisms (such as phytoplankton, zooplankton, and microorganisms) and sediments [58,59]. Moreover, SPM in the aqueous system is greatly affected by autochthonous production [60].…”
Section: Autochthonous Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autochthonous SPM production is imported from the resuspension of aquatic organisms (such as phytoplankton, zooplankton, and microorganisms) and sediments [58,59]. Moreover, SPM in the aqueous system is greatly affected by autochthonous production [60].…”
Section: Autochthonous Productionmentioning
confidence: 99%
“…Schmitt et al (2014) found that in the past 15 years, algal blooms frequently occurred in summer in Taihu Lake, and the accumulation of algal blooms increased the concentration of SPM in the lake [74]. In summer, algae-derived SPM was also shown to dominate in Taihu Lake and Sanwan (Gongshan Bay, Meiliang Bay, and Zhushan Bay) [34], and the occurrence of phytoplankton and algae had a significant impact on the stability of SPM [60]. In addition, a gradual temperature increase can result in rapid phytoplankton growth and an increase in autochthonous SPM in the water column as algal biomass increases [58].…”
Section: Phytoplanktonmentioning
confidence: 99%